The influence of e-hailing apps on urban mobilities in South Africa. Issue 3 (3rd July 2019) - Giddy, Julia Kathryn
ABSTRACT: E-hailing apps have played an important role in increasing mobilities in countries of the Global South. This study explores the ways in which e-hailing has influenced local urban mobilities using South Africa as a case study. Many trends were noted in this study of Johannesburg Uber users including an indication that Uber has generated a new userbase of taxi cab services. Results also showed the increased freedom Uber can provide by allowing individuals to move throughout the city due to its many safety features. Respondents feel that Uber has transformed both their personal mobilities and broad mobilities in South Africa.